Copper-catalyzed [4+2] oxidative annulation of α, β-unsaturated ketoxime acetates with ethyl trifluoropyruvate. Issue 47 (25th May 2022) - Yan, Huan; Xu, Gaochen; Gu, Meng; Zhang, Sai; Wu, Qinghuan; Meng, Jingjing; Zhu, Ning; Fang, Zheng; Duan, Jindian; Guo, Kai
Abstract : The copper-catalyzed [4+2] oxidative annulation of α, β-unsaturated ketoxime acetates with ethyl trifluoropyruvate for the synthesis of 2 H -1, 3-oxazines is described. Abstract : A novel route for tandem C–N/C–O formation via copper-catalyzed [4+2] oxidative annulation of α, β-unsaturated ketoxime acetates with ethyl trifluoropyruvate to synthesize valuable trifluoromethyl-containing 2 H -1, 3-oxazines in moderate to good yields is developed. This procedure represents the first [4+2] oxidative annulation of oxime derivatives with activated CO bonds and provides an alternative route towards functionalized 2 H -1, 3-oxazines.